Stakeholder priorities and conceptualization of One Health: Insights from fuzzy cognitive mapping and grounded theory - Evan F. Griffith; Angela Opondoh; Catherine Kaluwa; Erenius Lochede Nakadio; Kipkorir Rotich; Job Ronoh Kipkemoi; Jonah Levin; Jacob Mutua; Siobhan M. Mor; Janetrix Hellen Amuguni (PLoS ONE, 2026)
One Health (OH) has gained global recognition as a framework and practice for addressing interconnected health and sustainability challenges, such as emerging infectious diseases, food insecurity and climate change. Yet its operationalization remains limited, in part due to persistent differences in how OH is conceptualized across sectors and knowledge systems, including Indigenous knowledge holders and environmental actors. To address these gaps, we applied a mixed methods approach that combined fuzzy cognitive mapping (FCM) with grounded theory (GT) to examine stakeholder priorities and conceptualization of OH in Turkana County, Kenya. Thirty-six fuzzy cognitive maps were co-developed with community members, frontline workers, health, veterinary, and NGO stakeholders, then aggregated by group and analyzed using network metrics including normalized degree centrality and Jaccard similarity. Results revealed areas of alignment and convergence in OH conceptualization and perspective. Conceptually, the environment group map was the most distinct, while the health and NGO maps were the most similar. Environmental actors emphasized human-driven degradation, while community members described a pluralistic health system and the importance of wild foods, both absent from other group narratives. Shared priorities such as human and livestock health, nutrition, and water resources represent potential entry points for cross-sectoral integration. These findings demonstrate that barriers to OH operationalization are not only structural, but also shaped by differences in knowledge, experience, and problem framing across sectors and society within the socioecological system. Embedding ecosystem services, biodiversity, and traditional knowledge at the core of OH can enhance inclusivity and contextual relevance. Our integrated FCM-GT approach offers a transferable framework for participatory systems research, providing actionable insights for more inclusive and ecologically grounded OH implementation.